Clinico-epidemiological profile and treatment outcome of lip cancer: a retrospective study from north India - Tali, Tavseef Ahmad; Amin, Fiza; Khan, Nazir Ahmad; Dar, Javaid Ahmad; Sofi, Mushtaq Ahmad (International Journal of Research in Medical Sciences, 2023)
Background: Aim of present study to evaluate the Clinico-epidemiological profile and treatment outcome of Lip Cancer. Methods: This was a retrospective study performed in our hospital. All necessary clinical and epidemiological details of the 11 cases diagnosed with lip cancer from January 2016 to December 2021 were analysed. Results: The total number of new malignant cases diagnosed as lip cancer between January 2016 and December 2021 were 11, which comprised 6 male (55%) and 5 (45%) female. The male-to-female ratio was (1.2:1). The most common histological type was SCC, i.e., in 9 (81.8%) of the total number of cases and BCC was in 2 patients (18.2%). Overall survival at 5 years was 89% in our study. Conclusions: In conclusion, we have reported higher levels of lip cancer among men and those above 45 years of age. The important prognostic factors for overall survival in these patients were cancer stages. Better survival is achieved with surgery alone in the early stages and with adjuvant radiotherapy in the later stages.